2011
DOI: 10.1027/1618-3169/a000114
|View full text |Cite
|
Sign up to set email alerts
|

Exaggeration is Harder Than Understatement, but Practice Makes Perfect!

Abstract: Previous research on the fakeability of the Implicit Association Test (IAT) yielded inconsistent results. The present study simultaneously analyses several relevant factors: faking direction, type of instructions, and practice. Furthermore, it takes baseline individual differences into account. After a baseline assessment in a self-esteem IAT without faking instructions (t0), participants in the faking conditions then (t1) faked high or low scores without being provided with recommended strategies on how to do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 37 publications
1
79
0
Order By: Relevance
“…The latter seems problematic as faking becomes easier and more likely when test takers have greater knowledge about the test procedure (see, e. g., Dalen, Stanton, & Roberts, 2001). It is thus no wonder that the fakeability of the IAT has been well-documented (e. g., Fiedler & Bluemke, 2005;Röhner et al, 2011Röhner et al, , 2013Steffens, 2004) especially for the situation in which participants are informed about how the IAT works (i.e., informed faking; see, e. g., Röhner et al, 2011). The IAT is often used to assess socially stigmatized associations that might motivate people to fake (e. g., Agerström & Rooth, 2011;Banse et al, 2010;Banse et al, 2001;Carlsson & Björklund, 2010;Gray et al, 2005;Greenwald & Banaji, 1995;Greenwald et al, 1998;Latu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter seems problematic as faking becomes easier and more likely when test takers have greater knowledge about the test procedure (see, e. g., Dalen, Stanton, & Roberts, 2001). It is thus no wonder that the fakeability of the IAT has been well-documented (e. g., Fiedler & Bluemke, 2005;Röhner et al, 2011Röhner et al, , 2013Steffens, 2004) especially for the situation in which participants are informed about how the IAT works (i.e., informed faking; see, e. g., Röhner et al, 2011). The IAT is often used to assess socially stigmatized associations that might motivate people to fake (e. g., Agerström & Rooth, 2011;Banse et al, 2010;Banse et al, 2001;Carlsson & Björklund, 2010;Gray et al, 2005;Greenwald & Banaji, 1995;Greenwald et al, 1998;Latu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that the traditional IAT effect (i.e., the D measure; Greenwald et al, 2003aGreenwald et al, , 2003b contains not only variance related to the construct but also methodspecific variance (e. g., Back, Schmukle, & Egloff, 2005;McFarland & Crouch, 2002;Mierke & Klauer, 2003) and fakingrelated variance (e. g., De Houwer, Beckers, & Moors, 2007;Fiedler & Bluemke, 2005;McDaniel, Beier, Perkins, Goggin, & Frankel, 2009;Röhner, Schröder-Abé, & Schütz, 2011Steffens, 2004). Here, the diffusion model comes into play.…”
Section: The Traditional Iat Effect and Its Possible Contaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter might be of particular concern among researchers as not only has the fakeability of the IAT been well documented by many studies (Fiedler & Bluemke, 2005;Röhner et al, 2011Röhner et al, , 2013, but also, the IAT is often used to measure associations with socially stigmatized or sensitive topics (e.g., pedophilia, racism, stereotypes, and sexism; Greenwald et al, 1998;Agerström & Rooth, 2011;Banse, Schmidt, & Clarbour, 2010;Banse, Seise, & Zerbes, 2001;Carlsson & Björklund, 2010;Gray, Brown, MacCulloch, Smith, & Snowden, 2005;Greenwald & Banaji, 1995;Latu et al, 2011) which might increase the motivation to fake. Thus, a possible and welcome alternative to analyzing and interpreting the results of the IAT effect came from diffusion model analyses that can be applied to analyze the results of fast binary decision tasks, including the IAT (e.g., Klauer, Voss, Schmitz, & Teige-Mocigemba, 2007;Ratcliff, 1978Ratcliff, , 2014van Ravenzwaaij, van der Maas, & Wagenmakers, 2011;A.…”
Section: Introductionmentioning
confidence: 99%
“…This D measure, however, may sometimes be contaminated by construct-irrelevant sources of variance (e.g., method-specific variance; fakingrelated variance; Mierke & Klauer, 2003;Röhner, Schröder-Abé, & Schütz, 2011. The latter might be of particular concern among researchers as not only has the fakeability of the IAT been well documented by many studies (Fiedler & Bluemke, 2005;Röhner et al, 2011Röhner et al, , 2013, but also, the IAT is often used to measure associations with socially stigmatized or sensitive topics (e.g., pedophilia, racism, stereotypes, and sexism; Greenwald et al, 1998;Agerström & Rooth, 2011;Banse, Schmidt, & Clarbour, 2010;Banse, Seise, & Zerbes, 2001;Carlsson & Björklund, 2010;Gray, Brown, MacCulloch, Smith, & Snowden, 2005;Greenwald & Banaji, 1995;Latu et al, 2011) which might increase the motivation to fake.…”
Section: Introductionmentioning
confidence: 99%